2022
DOI: 10.1007/s00521-022-07206-4
|View full text |Cite
|
Sign up to set email alerts
|

Arabic fake news detection based on deep contextualized embedding models

Abstract: Social media is becoming a source of news for many people due to its ease and freedom of use. As a result, fake news has been spreading quickly and easily regardless of its credibility, especially in the last decade. Fake news publishers take advantage of critical situations such as the Covid-19 pandemic and the American presidential elections to affect societies negatively. Fake news can seriously impact society in many fields including politics, finance, sports, etc. Many studies have been conducted to help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Therefore, in this work, we have tried to figure out the performance of several models and their parameter tuning for the prediction of news containing false information about COVID-19. The proposed work is different from the study [22] discussed above in the sense that it evaluates eight DL classifiers for detecting fake news in the Arabic language. Whereas, our work evaluates six ML and two DL classifiers for the same task in the English language.…”
Section: Related Workmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, in this work, we have tried to figure out the performance of several models and their parameter tuning for the prediction of news containing false information about COVID-19. The proposed work is different from the study [22] discussed above in the sense that it evaluates eight DL classifiers for detecting fake news in the Arabic language. Whereas, our work evaluates six ML and two DL classifiers for the same task in the English language.…”
Section: Related Workmentioning
confidence: 89%
“…The authors developed transformer-based classifiers for the task. They constructed a dataset of fake news in the Arabic language for evaluating their proposed models, and achieved an accuracy score of more than 98 percent [22].…”
Section: Related Workmentioning
confidence: 99%
“…According to a study [33], False-Negative (FN) and False-Positive (FP) are important for rumor detection tasks. Misclassifying rumors as non-rumors, and vice versa, affects and misleads society by spreading untruthful news.…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that transformer-based models outperformed neural-based ones. While the study [33] detected fake news using eight BERT transformer-based models, two were multilingual, and the remaining were BERT models for the Arabic language.…”
Section: A Rumor Detection Using Unimodal Approachesmentioning
confidence: 99%
“…Fake news detection (FND) can be described as "the forecasting the probabilities of a specific news article (expose, news reports, editorials, and so on) being intentionally deceptive". Other terminologies regard tasks closely based on FND, adding credibility assessment, rumour detection, misleading data detection, stance classification of news articles, rumor veracity classification, checking "the valuation of news authenticity", and claiming confirmation [5,6]. Recently, FND tasks have grasped substantial attention from the natural language processing (NLP) research community.…”
Section: Introductionmentioning
confidence: 99%